Phosphaturic Mesenchymal Tumors: Clinicopathologic, Immunohistochemical and Molecular Analysis of 22 Cases Expanding their Morphologic and Immunophenotypic Spectrum - Agaimy, Abbas; Michal, Michael; Chiosea, Simion; Petersson, Fredrik; Hadravsky, Ladislav; Kristiansen, Glen; Horch, Raymund E.; Schmolders, Jan; Hartmann, Arndt; Haller, Florian; Michal, Michal (American Journal of Surgical Pathology, 2017)
Phosphaturic mesenchymal tumor (PMT) is a rare neoplasm of uncertain histogenesis that has been linked to tumor-induced osteomalacia (TIO) since 1959. The neoplastic cells produce increased amount of FGF23 which results in TIO via uncontrolled renal loss of phosphate (phosphaturia), and consequently diminished bone mineralization. To date, 300 cases have been reported. Although there is increasing evidence that PMT can be diagnosed by reproducible histopathologic features, firm diagnosis has been often restricted to cases associated with TIO and, hence, diagnosis of "nonphosphaturic variants" remained challenging. Recently, FGFR1/FN1 gene fusions were detected in roughly half of cases. We herein reviewed the clinicopathologic features of 22 PMTs (15 cases not published before), stained them with an extended immunohistochemical marker panel and examined them by fluorescence in situ hybridization for FGFR1 gene fusions. Patients were 12 males and 9 females (one of unknown sex) aged 33 to 83 years (median: 52 y). Lesions affected the soft tissues (n=11), bones (n=6), sinonasal tract (n=4), and unspecified site (n=1). Most lesions originated in the extremities (9 in the lower and 4 in the upper extremities). Acral sites were involved in 10 patients (6 foot/heel, 3 fingers/hands, and 1 in unspecified digit). Phosphaturia and TIO were recorded in 10/11 and 9/14 patients with detailed clinical data, respectively. Limited follow-up (5 mo to 14 y; median: 16 mo) was available for 14 patients. Local recurrence was noted in one patient and metastasis in another patient. Histologically, 11 tumors were purely of conventional mixed connective tissue type, 3 were chondromyxoid fibroma-like, 2 were hemangio-/glomangiopericytoma-like with giant cells, and 1 case each angiomyolipoma-like and reparative giant cell granuloma-like. Four tumors contained admixture of patterns (predominantly cellular with variable conventional component). Immunohistochemistry showed consistent expression of CD56 (11/11; 100%), ERG (19/21; 90%), SATB2 (19/21; 90%), and somatostatin receptor 2A (15/19; 79%), while other markers tested negative: DOG1 (0/17), beta-catenin (0/14), S100 protein (0/14), and STAT6 (0/7). FGFR1 fluorescence in situ hybridization was positive in 8/17 (47%) evaluable cases. These results add to the phenotypic delineation of PMT reporting for the first time consistent expression of SATB2 and excluding any phenotypic overlap with solitary fibrous tumor or sinonasal glomangiopericytoma. The unifying immunophenotype of the neoplastic cells irrespective of the histologic pattern suggests a specific disease entity with diverse morphotypes/variants rather than different neoplasms unified by TIO.
EVALuna2:6834